A brief excursus through the concept of the trust, dealing with its origins and history and generally traversing taxation of a trust and its implications for the taxpayer - De Mink, Jason (Centre for Law and Society, 2024)
A 'trust' is defined in the Income Tax Act [1] at section one as 'any trust fund consisting of cash or other assets which are administered and controlled by a person acting in a fiduciary capacity, where such person is appointed under a deed of trust or by agreement or under the will of a deceased person'. This is a recent introduction to the Act, coming into affect in respect of years of assessment ending on or after 1 January 1993 and sums up reasonably regarding satisfactorily what the various authorities have said to date trusts. In Estate Kemp v McDonald's Trustee [2] judge Solomons referred to the fact that in a trust the 'legal dominium of property is vested in the trustee' but that they have 'no beneficial interest in it but are bound to hold and apply it for the purpose of some persons or for the accomplishment of same purpose' [3] In Thome & Molenaar NNO v Receiver of Revenue, Cape Town [4] a trust was described as being 'created by contract, very often by contract of donation . . . or by way of a will. It is created in respect of defined administer property transferred to a trustee, who is burdened with the obligation to the property for the benefit of a third person’ [5]. In the case of Goodricke and Son (Pty) Ltd v Registrar of Deeds. Natal [6] the court held that the concept of a valid trust revolved around the removal of dominium (ownership) from the beneficiaries and placing it in the hands of the trustees [7]. ' ... [A] trust exists when property is to be held or administered by one person on behalf of another, or for some purpose other than his own benefit' [8]. The court went on to say that the essential elements which made up a trust were 'segregation of the trust assets by the founder' and the 'creation of an obligation to administer otherwise than purely for oneself' [9].